CORRELATION OF FAÇADE CHARACTERISTICS ON ENERGY AND DAYLIGHTING PERFORMANCE OPTIMIZATION OF OFFICE BUILDING (CASE STUDY: SATRIO TOWER, JAKARTA) - Madina, Rizki Fitria; Tundono, Sri; Rezandi, Fajar; Umara, Asyifa Putri; Nurrohman, Muhammad Lazuardy (Universitas Mercu Buana, 2024)
Energy-efficient building design is mandatory to obtain a building permit for new buildings in Jakarta. Greenship New Building is one of the green building assessment tools for new buildings in Indonesia compiled by the Green Building Council Indonesia. In the Energy Efficiency and Conservation category, points earned related to OTTV value and daylighting area are influenced by building facade design. This research aims to determine the correlation of building facade characteristics to energy and daylighting performance in office buildings to obtain the best performing building facade. This research uses Satrio Tower as a case study, a 26-story office building in the CBD Mega Kuningan area, South Jakarta. Data in the form of OTTV values were obtained through numerical simulations based on the OTTV formula from SNI 6389: 2020 and daylighting conditions in the building were obtained by conducting computational simulations using Dialux Evo. Then the building facade performance data is compared and analyzed for correlation. It was found that a design combining the use of a 60 cm horizontal shading device, the use of low-emissivity glass and a low window-wall ratio had the best energy and daylighting performance. Among the building facade characteristics, the visible light transmittance value of the glazing material has a positive correlation with the energy and daylighting performance.